Perancangan dan Implementasi Penyusunan Laporan Keuangan Berbasis SAK EMKM Melalui Spreadsheet Sebagai Solusi Digitalisasi Akuntansi Sederhana - Clarisa Diva Ramandani; Naila Evitasari; Masripah (Universitas Persada Indonesia YAI, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are key drivers of the Indonesian economy but often lackadequate financial reporting. Many MSMEs still record transactions manually and do not prepare financialreports in accordance with the SAK EMKM. This community service project aims to socialize andimplement a simple digital bookkeeping tool based on Spreadsheet to help MSMEs, particularly Nawneeds,to produce financial reports that comply with SAK EMKM. The implementation includes introducingaccounting concepts, transaction recording, and financial reports (income statement, balance sheet, andcash flow). The result shows improved understanding and willingness of business owners to adopt digitalbookkeeping using the provided template.Keywords: MSMEs, SAK EMKM, digital bookkeeping, financial report, Spreadsheet